Prediction of interfragmentary movement in fracture fixation constructs using a combination of finite element modeling and rigid body assumptions. Issue 15 (18th November 2021) - Mühling, M.; Winkler, M.; Augat, P.
Abstract: The amount of interfragmentary movement has been identified as a crucial factor for successful fracture healing. The aim of our study was to combine finite element analysis with a rigid body assumption to efficiently predict interfragmentary movement in fixed tibial fractures. The interfragmentary movement in a transverse tibial shaft fracture (AO/OTA type 42-A3) fixed with a locked plating construct was simulated using finite element analysis. In order to assess the contribution of the components on the resulting interfragmentary movement, the tibia, screws and embedding was either simulated deformable or as rigid body. The rigid and the deformable model accurately predicted the interfragmentary movement (R 2 = 0.99). The axial movement ranged between 0.1 mm and 1.3 mm and shear movements were between 0.2 mm and 0.5 mm. Differences between the two models were smaller than 73 μ m (axial) and 46 μ m (shear). The rigid body assumption reduced computation time and memory usage by up to 61% and 97%, respectively.